Effect of golimumab on health-related quality of life, other patient-reported outcomes and healthcare resource utilization in patients with moderate-to-severe ulcerative colitis: a real-world multicenter, noninterventional, observational study in Greece. Issue Volume 33:Issue S1(2021) (21st May 2021) - Gatopoulou, Anthia; Christodoulou, Dimitrios K.; Katsanos, Konstantinos H.; Bakos, Dimitrios; Mouzas, Ioannis; Tzouvala, Maria; Theodoropoulou, Angeliki; Paspatis, Gregorios; Theocharis, George; Thomopoulos, Konstantinos; Giouleme, Olga; Kourikou, Anastasia; et al.
Abstract : Background and aims: This real-world study assessed the impact of golimumab on health-related quality of life (HRQoL) and other patient-reported outcomes (PROs) in patients with ulcerative colitis over 12 months in Greece. Methods: GO-LIFE was a noninterventional, prospective, multicenter, 12-month study. Patients who had moderately-to-severely active ulcerative colitis were naïve to antitumor necrosis factor (anti-TNFα) therapy and had failed previous conventional therapy. Patients received golimumab as per label. The primary endpoint was patients achieving inflammatory bowel disease questionnaire 32-item (IBDQ-32) remission at 12 months. Secondary endpoints, at 6 and 12 months, included patients achieving IBDQ-32 response; the mean change in the treatment satisfaction questionnaire for medication (TSQM) and the work productivity and activity impairment in ulcerative colitis (WPAI:UC) questionnaires; changes in healthcare utilization; patients achieving clinical response and remission; adherence rates and the percentage of patients who discontinued golimumab. Results: IBDQ-32 remission was achieved by 76.9% of patients at 12 months. Mean changes in all TSQM and WPAI:UC domain scores at 12 months were statistically significant. Clinical remission was achieved by 49.4 and 50.6% of patients at 6 and 12 months, and clinical response by 59.3 and 56.8%, respectively. All patients but one (80/81) had high adherence (≥80%) to golimumab treatment over 12 months. Ulcerative colitis-related health care resource utilization was reduced during the follow-up period. Conclusions: In real-world settings, treatment with golimumab resulted in meaningful improvements in HRQoL and other PROs, and in disease activity at 6 and 12 months in patients with moderately-to-severely active ulcerative colitis who were naïve to anti-TNFa therapy.